A mobilização dos funcionários públicos civis, no contexto da Emenda Constitucional n° 41/2003 - Fernandes, Veneranda Acosta (2016)
The actual work had for object of study the mobilization process of the public civil servants in Brazil, at the forefront of the pension counter-reform, accomplished through the Constitutional Amendment no 41/2003, which changed the rules and the structure of the Social Security Special Policies. The general aim is to analyze the path of organization and mobilization by the public civil servants, within the context of the pension counter-reform. A historical nature research was developed, using the historical Marxist Tendency. As a source of research bibliographies and documents, were used analyzing laws, books, parliamentary papers, articles, essays, dissertations, newspaper articles and virtual news related to pension counter-reform and the civil servants trade association, in particular, the mobilization performed in 2003. Also were performed interviews with class representative which were involved in the EC no 41/2003 approval legislative process. These interviews allowed the rescue of the memory about situations or actions of resistance that had not been registered in an institutional manner, and thus allowed us to know the class representatives perspective about what they had lived in that time. Observe that historically, the Brazilian public service was made from the perspective of a public patrimonial administration, based on the patronage and in the politic indication to occupy positions, excluding the basic principles of classical bureaucracy, which is the stability of positions and the selection by public exam. Such principles only were implemented, from the Federal Constitution of 1988 that contributed to an ambiguous training of this category of workers. With the advent of the model of flexible accumulation, a new stage of capitalism, the social rights and the structure of Brazilian public administration had conditional amendments, reflecting on social security, specially, the Special Social Welfare Policy. Such alterations in relation to the Special Social Welfare Policy were commanded by the government of the Worker’s Party – PT, which assumed a neo-liberal guideline after being elected to the Republic Presidency. The conclusion is that the counter-reform accomplished through the EC no 41/2003 did not have as aim the correction of system distortions, as propagated by the government, and is in fact, motivated by two main features: the obedience to the Washington Consensus’s neoliberal guidelines and the implementation a power national project, by PT, on the basis of the expansion of pension funds through the State capitalism. The most difficulty faced by the representative entities of the public civil servants, during the mobilizations held in 2003, were in relation to the maneuvers of the government in the National Congress, the strong media support that considered the functionalism as a privileged category, and the entities co-optation and the classists representatives, in order to induce the approval of government’s proposal. Besides, of course, in the economic and politic context that put pressure on the State reordering, and a certain degree of current social regulation. Therefore, the current challenge of Brazilian union movement, its structuring a new entity capable to protect the interests of the working class as a whole, even with all its heterogeneity.